Students’ Experience on Google Doc Use in Final Research Project Consultation - Nila Erdiani; Zulkipli Lessy (IJER (Indonesian Journal of Educational Research), 2022)
This study aims to investigate EFL students’ experience on Google Doc use in the final research project consultation. The participants in this research were students from the English Education Department. It consisted of eight students, five students from class A and three students from class B. The students are 20 to 22 years old. This study used a reflection sheet. The qualitative data were analyzed using students’ reflections based on usability concepts. Data analysis is carried out after the data is collected in Google form. The results of the study, in terms of Learnability, reveal that the Google Doc platform facilitates students in the online consultation process. Satisfaction revealed that students were satisfied with the use of Google Doc because there are many features available on the platform. The errors of the user in Google Doc during the final research project consultation showing the number of mistakes made by the users.